Pengaruh Literasi Keuangan Terhadap Keputusan Investasi (Studi Eksperimen di Gugus V Mandara Giri Kec. Kubutambahan) - Kadek Prita Ary Astini; Gede Wiadnyana Pasek (Universitas Pendidikan Ganesha, 2022)
This study aims to compare respondents' investment choices made before and after receiving financial literacy. The population of this research is the teachers in Cluster V Mandara Giri in Kubutambahan District. This study uses quantitative approaches and the data were collected through the dissemination of questionnaires throughout experimental research. All primary schools in Cluster V Mandara Giri, Kubutambahan District made up the study's sample. Moreover, this study utilizes the aid of SPSS 27.0 for Windows with a paired sample T-test data analysis method. The findings demonstrated that financial literacy has a positive impact on investment decisions. Keyword : Investment Decisions, Financial Literacy, Experimental Studi